3(x-1)-11=7

Simple and best practice solution for 3(x-1)-11=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)-11=7 equation:


Simplifying
3(x + -1) + -11 = 7

Reorder the terms:
3(-1 + x) + -11 = 7
(-1 * 3 + x * 3) + -11 = 7
(-3 + 3x) + -11 = 7

Reorder the terms:
-3 + -11 + 3x = 7

Combine like terms: -3 + -11 = -14
-14 + 3x = 7

Solving
-14 + 3x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 3x = 7 + 14

Combine like terms: -14 + 14 = 0
0 + 3x = 7 + 14
3x = 7 + 14

Combine like terms: 7 + 14 = 21
3x = 21

Divide each side by '3'.
x = 7

Simplifying
x = 7

See similar equations:

| x=5+0,5x | | 139-7x=20x+19 | | x^3+x^2-3x+8=9 | | 39=5u-16 | | 10-8x=50-36x | | x+0,5x=x | | 7x+32=2x+12 | | 6n+6-9=6n | | 4x^4+25x^2-160=0 | | 0=(x+7)*(2X+3) | | 162-6x=4+22 | | 0=2x-70 | | -6w+3(w+2)=-18 | | 6x-9=21-3 | | 3(x-5)+14=2(x+1) | | 3x-10=3x+4 | | 2(x-5)-10=x+7 | | 10y+6=5y-19 | | 2(x+3)-18=0 | | 7a+8b=15ab | | 3-1(2x+8)=-(3x-2) | | 7y-4=3y+8 | | y=-5x^2+50x-129 | | 24=2(8+w)+2w | | 3(u-4)-6u=-27 | | 4(2x-3)=3x+6 | | -17=2w+7-5w | | x+3=2x+y | | -7x=70 | | -45=b-17 | | 85+8y=29 | | 4+x=12-6 |

Equations solver categories